Clinical case of Malassezia otitis media in a dog - M. I. Chupryna (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Dermatopathologies are pretty standard among domestic dogs and cats. Today, Malassezia occupies a leading place among fungal skin lesions. Particular attention should be paid to Malassezia otitis since fungal infections are usually a marker of low resistance, so against their background, it is natural to increase the pathogenic effect of other microflora and, as a result, damage to the eardrum, middle ear, and other destructive changes in the hearing organs. The article presents the results of the use of a bioregulatory approach in the complex therapy of malassezia otitis in dogs with the use of the drug “Traumeel”, which contains ultra-low doses of biologically active substances. The use of this drug increases the safety of treatment, which in turn protects the animal's body from complications and adverse effects of therapy. The study was conducted based on a private outpatient clinic of veterinary medicine in Ternopil during the treatment of an 11-year-old dog with chronic otitis. The clinical manifestation of Malassezia otitis was determined by characteristic clinical signs (hyperpigmentation, hyperemia, edema, pain, and increased ceruminous secretion). A cytological examination with light microscopy of adhesive strips with biomaterial fixed on a slide and stained with a modified Wright-Giemza stain, “Leukodif”, was performed to confirm the diagnosis. For therapy, initially, a generally accepted standard therapy was used using 1 % ketoconazole and 2 % chlorhexidine twice a day and preliminary cleaning of the auricles. Since no positive dynamics were observed, Traumeel 1 ml intramuscularly 1 time per day for 5 days was additionally used for therapy. The choice of bioregulatory drug was based on the components and their action. After 7 days, the dog's inflammation significantly decreased – edema, hyperemia, and itching disappeared, and there was no pathological accumulation of ceruminous gland secretion. Subsequently, three more injections of Traumeel were performed with an interval of 48 hours. 3 weeks after the diagnosis, a repeated cytological examination for the presence of Malassezia was performed – the result was negative. Subsequently, the dog underwent hygienic ear cleaning 1–2 times a week. There were no relapses. Based on the therapy results, it can be concluded that the treatment regimen for Malassezia otitis is effective.